Impact of mobile payment on physical health: Evidence from the 2017 China household finance survey - Zhang, Rui; Zhang, Yunzhi; Xia, Jiahui (Frontiers in Public Health, 2022)
Individuals' health status is an essential indicator of the overall strength of a country. Existing literature has studied the determinants of individuals' health, but there is no direct evidence to date on the impact of mobile payment on health. To supplement relevant research and provide insightful policy suggestions to families, government and societies, based on data of 32,058 observations from the 2017 China Household Finance Survey, we estimate the effects of mobile payment on physical health using ordinary least squares and two-stage least squares strategy. This paper provides direct evidence that mobile payment has a positive impact on citizens' physical health. Heterogeneity analysis shows that mobile payment has a more profound impact on the health of citizens who are rural and less educated. Finally, further findings in this paper suggest that commercial insurance and leisure consumption are the mechanism through which the link between mobile payment and individuals' health operates.